Integrative systems biology and in-vitro analysis of cryptolepine’s therapeutic role in breast cancer - Hina Qayoom; Pankaj Keshari; Manzoor A. Mir (Discover Oncology)
Abstract Background Breast cancer is the most diagnosed cancer in women and the second leading cause of cancer-related deaths worldwide. Chemotherapy faces challenges like drug resistance, side effects, and recurrence, underscoring the need for innovative therapies. This study explores cryptolepine, a natural compound, for its therapeutic potential against heterogeneous BC by targeting specific molecular mechanisms. Methods we conducted an ADMET analysis to assess cryptolepine’s pharmacokinetic properties and drug-likeness. Target prediction was performed using SWISS-TARGET-PREDICTION and Integrative Pharmacology for BC. Identified targets were cross-referenced with BC-related genes from Gene Atlas, TCGA, and OMIM. Protein–protein interactions were analyzed using STRING, and pathway enrichment was assessed using KEGG and ShinyGO. Molecular docking and dynamics simulations evaluated cryptolepine’s binding efficacy while in-vitro assays, including proliferation studies and mRNA expression analysis, validated these findings. Results Cryptolepine demonstrated favorable drug-likeness and multi-target activity, interacting with key cancer pathways such as p53, STAT3, and PI3K-Akt. Network pharmacology revealed its potential to reduce drug resistance. Cryptolepine regulated important genes (PTGS2, STAT3, CCND1) across critical pathways (cAMP, PI3K/AKT, P53, IL6/JAK2/STAT3). Molecular docking confirmed strong binding (ΔG − 8.2 kcal/mol), and in-vitro assays showed IC50 values of 4.6 μM for MDA-MB-231 and 3.1 μM for Mcf-7. mRNA expression analysis indicated increased cytochrome C and BAX, while pro-caspase levels decreased. Conclusion Cryptolepine shows promise as a therapeutic candidate for BC. Future research should optimize its pharmacological profile for specificity and reduced toxicity. Graphical Abstract